Vulnerability mapping as a tool to manage the environmental impacts of oil and gas extraction. Issue 11 (29th November 2017) - Esterhuyse, Surina; Sokolic, Frank; Redelinghuys, Nola; Avenant, Marinda; Kijko, Andrzej; Glazewski, Jan; Plit, Lisa; Kemp, Marthie; Smit, Ansie; Vos, A. Tascha; von Maltitz, Michael J.
Abstract : Various biophysical and socio-economic impacts may be associated with unconventional oil and gas (UOG) extraction. A vulnerability map may assist governments during environmental assessments, spatial planning and the regulation of UOG extraction, as well as decision-making around UOG extraction in fragile areas. A regional interactive vulnerability map was developed for UOG extraction in South Africa. This map covers groundwater, surface water, vegetation, socio-economics and seismicity as mapping themes, based on impacts that may emanate from UOG extraction. The mapping themes were developed using a normative approach, where expert input during the identification and classification of vulnerability indicators may increase the acceptability of the resultant map. This article describes the development of the interactive vulnerability map for South Africa, where UOG extraction is not yet allowed and where regulations are still being developed to manage this activity. The importance and policy implications of using vulnerability maps for managing UOG extraction impacts in countries where UOG extraction is planned are highlighted in this article.